Pengaruh Kecakapan Manajerial Terhadap Kualitas Laba: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2015 - Amelia Roza Yulianda; Nurzi Sebrina (Universitas Negeri Padang, 2017)
This study aims to examine the relation between managerial ability and earnings quality of manufacture companies listed on Indonesian Stock Exchange period of 2010 to 2015. By using purposive sampling method, there were 62 companies as the research’s sample. In this study, earnings persistence and accruals quality were used to measure earnings quality. While MA-Score was used to measure managerial ability. Using panel regression analysis, this study shows that managerial ability has a significant positive effect on earnings persistence and accruals quality. According to the results, managerial ability had an effect on earnings quality.Keywords: managerial ability, earnings quality, earnings persistence,accruals quality